PENGARUH INOVASI DAN KREATIVITAS TERHADAP ENTREPRENEURIAL MARKETING DALAM UPAYA MENINGKATKAN KINERJA PEMASARAN - Ni Putu Yeni Astiti; Ni Noman Ari Novarini (Forum Manajemen STIMI Handayani Denpasar, 2019)
An industry that is successful in its business is an industry that is able to create the right strategy formulation, because the right strategy can determine the success of Small and Medium Enterprises can compete in the global market. The purpose of this study is to determine the effect of innovation on entrepreneurial marketing, creativity on entrepreneurial marketing and the influence of entrepreneurial marketing on marketing performance. The population in this study were the Small and Medium Enterprises actors whose sales systems were carried out using the Entrepreneurial Marketing system. In this study the number of indicators used was 21 x 10. So, the number of samples determined was 210 respondents. The sample determination technique used in this study is based on purposive sampling technique, namely sampling based on criteria. The criteria for selecting a sample are the actors of Small and Medium Enterprises who apply the concept of Entrepreneurial Marketing in their business. The next step is accidental sampling, which is the sampling technique that is carried out on Small and Medium Enterprises actors that are easy to find. Data analysis method used is Structural Equation Model (SEM) from the PLS statistical package. Results of Innovation Research have a positive and significant effect on Entreprenuerial Marketing in Small and Medium Enterprises in Denpasar City. Creativity has a positive and significant effect on Entreprenuerial Marketing in Small and Medium Enterprises in Denpasar City. Entreprenuerial Marketing has a positive and significant effect on curious performance.